An online survey on the association between the use of alcohol-based hand sanitizer and dermatitis in the Jizan Population - Mona H. EL-Mahdy; Nada M. Makeen; Zenat A. Khrid; Khawla Mohammed Modawi; Maram Abdullah Sayegh; Amnah Hussain Hamrani; Anisah Mohammed Humedi; Shumokh Fawaz Juraybi; Sharifah Abdulrahman Someli; Shatha Ahmed Darbashi; Wafa Mohammed Busayli (Journal of Family Medicine and Primary Care)
Background: Frequent use of alcohol-based hand sanitizers during the COVID-19 pandemic can cause skin irritation and dermatitis due to the removal of natural skin oils. This survey aims to assess the association between alcohol-based hand sanitizer use and dermatitis prevalence among the residents of Jizan, Saudi Arabia. Methods: This cross-sectional study was conducted using an online survey distributed between September and December 2021. The survey collected data on hand sanitizer usage patterns, dermatitis symptoms, and sociodemographic characteristics of 500 randomly selected Jizan residents aged ≥18 years. Associations between sanitizer use variables and dermatitis occurrence were analyzed using Chi-square and exact probability tests for instances with low frequencies. Results: The majority were 347 (69.4%) females, with a mean age of 23.6 ± 11.8 years. A total of 402 (80.4%) used sanitizers, increasing to 395 (79%) during the pandemic. Dermatitis symptoms were reported in 138 patients (27.6%) after sanitizer use. Using sanitizers >6 times daily was associated with 71.4% a dermatitis prevalence of 47.4% versus <3 times daily (P = 0.003). The use of 80–95% alcohol gels was linked to 68.8% dermatitis versus other products (P = 0.001). The common symptoms included skin roughness (55.4%), itching (46.5%), and redness (37.6%). Onset was immediate (23.3%) and within hours or days (28.2%). Conclusions: This study demonstrated a clear association between frequent or high-concentration sanitizer use and increased dermatitis prevalence among Jizan residents. Public awareness campaigns and product guidelines are needed to promote proper usage of techniques that balance hygiene and skin health. Future research should explore effective prevention strategies, such as moisturizer combinations or lower risk alternatives.